Reminding system for safety smartphone using to reduce symptoms of computer vision syndrome - Watcharee Jumpamule (2019)
© 2018 IEEE. Prevention or reduction of the symptoms of Computer Vision Syndrome (CVS) can be done by following the 20-20-20 rule (take a 20-second break to view something 20 feet away every 20 minutes). Hence, an intelligent tool is required to encourage the user following this rule and aware of a computer safety-using. This paper proposes a new reminder system which constantly monitors the use of a smartphone in real time for periodic breaks (and produces a warning and some practical advice) to slow down at least one level of CVS symptoms. The proposed system was conducted in four main phases: study and collect data, analysis and design, implementation, and experiment phases. This system has four main features: user interaction detection, use/pause time counting, alarm making, advice display and object distance estimation. For a continuous usage period, we calculate from the interval of user interaction, i.e. screen touching, keystroke, mouse move and a light sensor. For a warning break, we used a rule-based alarm. Furthermore, the proposed system captures the computer-using behavior by recording a usage and pause time for each use period. The experiment results showed that the smartphone using which this proposed system installed, can statistical significantly reduce a symptom level of burning eye for all user, but for other symptoms reduction statistically, depend upon each user. User satisfaction of this system is scored for 8.2 of 10.